Occupational Overuse Syndrome and its Severities in Software Professionals of Rupandehi District, Nepal - Dhakal, Indra; Sharma, Shanta (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Prevalence of occupational overuse syndrome (OOS) is not new in computer professionals. Occupational overuse syndromes are diseases of the modern era and rank first among the health problems in the frequency with which they affect the quality of life. As the IT has been developed in a rapid way the different health problems are emerging in the same way which is of great concern. Some are caused by occupational exposures, and are marked with direct professional relation, or the action of harmful effects in the workplace. MATERIAL & METHODS: A descriptive study was conducted in software professionals of Rupandehi district, Nepal. Data was collected as per pretested structured Performa from 270 respondents randomly and analyzed by using SPSS, MS-excel and Chi-square test to determine associations between categorical variables. RESULTS: The results of the study showed that majority of respondents belonged to 20-30 years of age, 74.4 per cent of respondents were male and 25.6 per cent were female, major occupational overuse syndrome was headache, back pain and neck pain. Majority of respondent's (56.3%) working duration was 3-6 years and increased health problems are observed with increase in work duration. CONCLUSION: The present study concluded that majority of respondents had health problems and the major occupational overuse syndromes were headache, back pains, neck pain. Study also concludes that there is a relation between working duration and health problems, and the problems increase as the duration at work increases. Journal of Universal College of Medical Sciences, Vol. 5, No, 2, 2017, Page: 26-30